KESETARAAN LAYANAN BPJS KESEHATAN BERBASIS MODEL EVALUASI PROGRAM IKEP RSUD AHMAD YANI KOTA METRO - Gusnita, Ari; Rakhmadani, Syeni; Mulyono, Joko; Ari Gusnita; Syeni Rakhmadani; Joko Mulyono (JURNAL TAPIS, 2023)
Inequalities in access and health services for BPJS users include not all medicines being covered, difficulty in checking or receiving treatment, difficulty in getting a room, and several other complaints. The aim of this research is to determine the IKEP model Problem Identification, Confirmation, Evaluation and Improvement) for implementers and administrators of BPJS Health at RSUAD A. Yani, Metro City. This research uses empirical juridical research methods with descriptive, explanatory and prescriptive approaches. Data collection methods consist of literature and documentation of observations and interviews. The data analysis method used is a qualitative analysis method. The results of the research conducted by researchers found in the field that problems occurred in the facilities and infrastructure as well as BPJS services related to the online system, both in registration and in the referral system. Another problem also occurs in the HR system which is lacking and less professional in providing services. Therefore, researchers offer suggestions in the form of an IKEP MODEL at RSUD A Yani, Metro City to help organize services better, including with leadership, organizational culture, institutions, SOPs, management of public complaints, control and evaluation and human resources.